Magnetic Characterization of Fine Sediment in the Solo Basin Indonesia - Budi Legowo; Anti Fatkhul Qoiriah; Artono Dwijo Sutomo; Shandiyano Putra; Wiwit Suryanto; Budi Purnama (Journal of Mathematical and Fundamental Sciences, 2023)
The magnetic characteristics of fine sediment samples from the Solo Basin are reported in this paper. Magnetic fine sediment was identified by magnetic susceptibility mapping based on sampling of 182 points. Then, a depth analysis (on 7 selected sampling points) was performed using X-ray fluorescence spectrometry, which showed an iron oxide content of up to 55.42%, while X-ray diffractometry confirmed magnetite minerals with crystallite size ≤100 nm. Further, the vibrating sample magnetometry results verified the magnetic characteristics under a single-domain configuration. The characteristic magnetic susceptibility map showed that there is a lithogenic effect on sediment in the Solo Basin. In addition, anthropogenic activities seem to play a pivotal role in distributing magnetic materials.